Mercury: biogeochemical and toxicological aspects and levels found in marine fish in the Southern Brazilian coast - Rodrigues, Marcelo Tardelli (2015)
Sources of mercury (Hg ) introduced into the environment can be natural or anthropogenic. Methylmercury (MeHg ) is the most toxic form of the mercury, and is responsible for detrimental e ects on human health through the consumption of food, notably marine vertebrates such as carnivorous fish and sharks. is review focuses on aspects related to biogeochemistry and ecotoxicology of mercury in aquatic environments and presents 12 studies with sh in the Southern Brazilian coast marine environment where 50% of the sh sampled had Hg concentrations, above the level established by national and international agencies as safe for human consumption.